Strategies to strengthen non-governmental organizations' participation in the Iranian health system - Arman Sanadgol; Leila Doshmangir; Leila Doshmangir; Reza Majdzadeh; Vladimir Sergeevich Gordeev; Vladimir Sergeevich Gordeev (Frontiers Media S.A., 2022)
BackgroundNon-governmental organizations (NGOs) added a new dimension to intersectoral action for health. Involving the NGOs in health system strengthening could lead to a more efficient, equitable, and better-governed healthcare system. This qualitative study explored effective strategies for NGO participation in the Iranian health system to achieve broader health system goals.MethodWe conducted 33 semi-structured interviews with health policymakers and planners, NGO actors at the national and provincial levels, and other key informants. The qualitative data were analyzed through a thematic analysis approach. Trustworthiness in the study was observed at all stages of the study.ResultFour main themes- were identified: empowerment for learning leadership and management skills, creating active participation in policy-making, capacity building for participation, clarifying participation process, falling into 17 sub-themes. Along with the government and health sector policymakers, NGOs may have a significant role in improving health system goals and increasing equity, social responsiveness, financial risk protection, and efficiency.ConclusionThe participation of NGOs in the Iranian health system is a complex process. All elements and dimensions of this process need to be considered when developing a platform for the appropriate participation of NGOs in the health system functions. Evidence-informed strategies for strengthening the participation of NGOs in the health system should be used to utilize NGOs potential to the fullest.